THE METHOD OF GUESSING GAME THROUGH PICTURES AS THE ALTERNATIVE TO MOTIVATE THE STUDENTS TO IMPROVE THEIR SPEAKING SKILL - Punawar Punawar (English Language Teaching Department (Prodi Pendidikan Bahasa Inggris), 2019)
Abstract. In teaching language, a teacher needs to apply a certain approach, method, and technique or strategy in order to get the good result in teaching. This study is aimed to know how the Guessing Games through Pictures can motivate students to improve their speaking skill in class XI-IPS.1 and XI-IPS.2 in odd semester at 2019/2020. The Methodology of the study is a classroom action research. The method is chosen because the writer is quite sad and concerned to find the fact that the students’ speaking skill is really poor. The data involved four aspects for their speaking skill. They are fluency, pronunciation, vocabulary and grammar. While students communicative competence also covered four aspects. They are the student ability in raising question, ability in giving responses, ability in giving explanation and ability in giving description. Rubric of the students speaking score and the form of the students’ demonstrated competence were used to record their both speaking skill and demonstrated competence. While the student active participation and motivation was scored by using the form of checklist. The score or the data was analyzed from cycle to cycle to make sure whether there was progress or not. The result of the study showed that based on the finding of the data from two cycles there was an increase in almost all aspects in students speaking skill and the students’ activeness in joining the process of learning in class. The data obtained show very significant progress although the result of first stage with 2 cycles is that the students did not achieve the criteria of success because their average score was only 61.32. But the score is much better than the result before implementing the method that is only 41.36. Then the result of stage 2 with 2 cycles has proved that most of the students have achieved the criteria of success for the average score gained by the students was 76.55. Pronunciation was the most difficult aspect in students speaking skill. This was quite logic since aspect of pronunciation in the students speaking skill and aspect of describing in students demonstrated competence were the most difficult and complicated problem faced during the speaking classroom activities.